2020
DOI: 10.21873/anticanres.14503
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Newly Synthesized Platinum(IV) Complexes on Cytotoxicity and Radiosensitization of Human Tumour CellsIn Vitro

Abstract: Aim: Newly synthesized platinum(IV) complexes with ethylenediamine-N,N'-diacetate ligands (EDDA-type) (butyl-Pt and pentyl-Pt) were investigated against two cancer (A549 lung, and HTB 140 melanoma) and one noncancerous (MRC-5 embryonic lung fibroblast) human cell lines. Materials and Methods: The effects of these agents were compared with those of cisplatin after 6-, 24-and 48-h treatment. Sulforhodamine-B (SRB) assay was performed to estimate the cytotoxic effect, while the inhibitory effect on cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In the area of non-platinum complexes, various complexes containing gold, copper, ruthenium, and palladium have shown a strong cytotoxic effect on different cancer cell lines (6)(7)(8)(9). Also, many of these non-platinum complexes showed a high degree of selectivity which means they had a low effect on the viability of healthy cells in vitro (10)(11)(12). Therefore, transition metals represent the future in the treatment of different types of cisplatin-resistant cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the area of non-platinum complexes, various complexes containing gold, copper, ruthenium, and palladium have shown a strong cytotoxic effect on different cancer cell lines (6)(7)(8)(9). Also, many of these non-platinum complexes showed a high degree of selectivity which means they had a low effect on the viability of healthy cells in vitro (10)(11)(12). Therefore, transition metals represent the future in the treatment of different types of cisplatin-resistant cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, about 30 new compounds entered some phase of the clinical trial. Yet, only a few have been introduced into clinical practice (Gibson, 2019; Jurišević et al, 2016; Petrović et al, 2020). Among others, Pt complexes with diamine ligands are in the field of interest as well.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, Pt complexes with diamine ligands are in the field of interest as well. The literature data showed that Pt(II/IV) complexes with edda (ethylenediamine‐ N , N′ ‐diacetate)‐a type of ligands had considerable effects on various cancer cell lines with promising potential to overcome cisplatin‐resistance (Dimitrijević et al, 2013; Jurišević et al, 2016; Petrović et al, 2020; Stojković et al, 2014). Pt(IV) complexes with bidentate N , N′ ‐ligand precursors, O , O ′‐dialkyl esters (alkyl = ethyl, propyl, butyl) of ethylenediamine‐ N , N′ ‐di‐ S , S ‐(2,2′‐dibenzyl) acetic acid (Pt(IV) eddba complexes), used in this study, previously showed extremely stronger antiproliferative potential than cisplatin on freshly isolated chronic lymphocytic leukemia cells (Dimitrijević et al, 2013), but also high toxicity on female rat liver (Paunović et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation